(untitled) (Baghdad Science Journal, 2009)
Blogging is about more than just putting thoughts on a web; it’s about connecting with and hearing from anyone who read the work. Many web sites now days help to get a free account to quick post thoughts and photos interact with people, and more. The fastest way to understand blogging is to try it out, but in that case securing the blog is important, by including authentication schemes. In this paper we suggest implications of our research for improving the design and usefulness of blogging systems, and also we divided the blogs depending on the subject and need, which are either to be used in public or only used by small group, so we can suggest different steps for securing the blogs.